PENGARUH RETURN ON EQUITY, ARUS KAS AKTIVITAS OPERASI, UKURAN PERUSAHAAN, DAN DEBT-TO-EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ 45 DI BURSA EFEK INDONESIA PERIODE 2012—2015 - Lasmanita Rajagukguk; Cindy Lourenta Wijono; Yunus Pakpahan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2018)
Investments are performed in order to receive return. Return is the amount generated on an investment relative to the cost of investment.Stock return determines the value of a firm. Investors would consider investing in attractive companies, i.e. those with high stock returns. This research aims to analyze the effects of return on equity, operating cash flow, firm size, and debt-to-equity ratio on stock return for corporations included on the LQ45 Index on Indonesian Stock Exchange, from 2012-2015. Firm size was measured with end-of-year total assets. The data of this research were extracted from the financial reports of the observed corporations. Observations included 20 companies that appeared on the LQ45 index during 2012 until 2015. It is found that return on equity and operating cash flow significantly influence stock return, whereas firm size and debt-to-equity ratio do not affect stock return.